The broadband multichannel UHF transmitting TV antenna - Kudzin, V. P.; Sannikov, N. J. (Видавництво Національного університету "Львівська політехніка", 2009)
The broadband multichannel UHF transmitting TV antenna consisting of shunt dipoles is offered. The antenna works on several frequency channels simultaneously. The detailed numerical and experimental research is carried out and the geometry of the antenna is optimized. The structure of the antenna includes two orthogonal planes of radiators, the power divider and matching device. The industrial sample of the aerial is created.
Keywords: transmitting antenna; UHF band; integral equations